Welcome to Ireland: Seeking Protection as an Asylum Seeker or through Resettlement—Different Avenues, Different Reception - Kinlen, Louise (Refuge: Canada's Journal on Refugees, 2013)
Ireland accepts approximately 200 resettled refugees each year under the UNHCR Resettlement Programme and a range of supports are put in place to assist the refugees when they arrive and to help their process of integration into Irish society. Roughly ten times this number of asylum seekers arrives in Ireland each year, with some coming from similar regions and groups as the resettled refugees. The reception conditions of both groups however are remarkably different, with a number of grave humanitarian concerns having been raised about the reception conditions of asylum seekers. This article explores the background to refugee reception in Ireland, the current reception conditions of the two groups, how they differ and an analysis of whether such treatment is justifiable.